Microfiltração e ultrafiltração para tratamento de águas de chuva coletadas em solo - Sandoval, Abby Daniela Ortega (2016)
The management of stormwater runoff has been a topic of discussion for problems at urban and rural level: floods, failure of drainage system and pollution of water bodies. As a solution, the implantation of rainwater harvesting systems has been driven in the last decades to reach needs that do not require purifying process such as flushing toilets, irrigation, cleaning and cooling spaces, but also for potable use. Catchment areas commonly used are the roofs of the buildings, taking advantage of its slope and, in theory, the lowest degree of pollution. However, there is a lack of research in modern rainwater harvesting systems, on the lookout for new areas of catchment and proper treatment to achieve the quality levels. In the interest of sustainable management of stormwater runoffs, this work addresses the stormwater harvesting using a university parking lot as catchment area, studying membrane technology as a treatment technique to suit this water. The stormwater was collected through a system placed inside the drain sewer, taking advantage of gravity flow. In the first experimental stage, the flux variation and rejections of the MF and UF were evaluated, working with two operating pressures: 10 and 40 kPa. With 40 kPa pressure greater efficiencies were observed in the removal of organic matter, both in MF and UF. For the second stage, continue operation tests were applied between 4,5 and 8 hours, with both membrane separation processes. The stormwater and the permeate were characterized by 27 physical, chemical and microbiological parameters, including heavy metals, nutrients, hydrocarbons and fecal coliforms. Color, turbidity, metals and oil and greasevalues presented concentrations above of similar studies. The removal efficiency in MF and UF was above 90% for suspended solids and coliforms, but for hardness, nitrate and sulfate, rejections were low. The UF membrane presented a better performance in flow behaviour and removal of Fe, Ni and total solids. The application prospects were determined by evaluating the permeate quality with guidelines of Brazil, United States, Australia and Spain. It had also been proposed a treatment system in situ. Therefore, the management of stormwater runoff by micro and ultrafiltration treatment is a very attractive option for urban uses, reducing local risks and pollution that reaches water bodies.